The Impact of Quality of Work Life on Employee Performance of PT. Tunas Dwipa Matra Lampung - Kintan Dwi Amelia; Zunaidah Zunaidah; Muhammad Ichsan Hadjri (Journal Research of Social Science, Economics, and Management, 2024)
This research was conducted to determine the effect of Quality of Work Life (QWL) on employee performance, with an empirical study carried out at PT. Tunas Dwipa Matra Lampung. The population in this study consisted of all employees at PT. Tunas Dwipa Matra Lampung, totaling 442 employees. The sampling technique used was simple random sampling, in which the Slovin formula was applied to the total population of 442 employees with a 5% margin of error. This resulted in 211 employees being selected as the sample for this study. The research employed multiple linear regression analysis to evaluate the data. The findings indicate that Quality of Work Life has a positive and significant effect on employee performance. Key aspects of QWL, such as employee welfare, including providing recreation, should be prioritized by companies to help reduce stress and anxiety. Improving mental health through such initiatives can positively impact employee performance, ultimately benefiting the organization. Therefore, enhancing QWL is an important factor in increasing employee motivation, job satisfaction, and overall productivity.